2012
DOI: 10.1128/jb.01544-12
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Ribosomal Protein Genes in Bacillus subtilis Reveals Importance of Each Ribosomal Protein for Cell Proliferation and Cell Differentiation

Abstract: bAmong the 57 genes that encode ribosomal proteins in the genome of Bacillus subtilis, a Gram-positive bacterium, 50 genes were targeted by systematic inactivation. Individual deletion mutants of 16 ribosomal proteins (L1, L9, L15, L22, L23, L28, L29, L32, L33.1, L33.2, L34, L35, L36, S6, S20, and S21) were obtained successfully. In conjunction with previous reports, 22 ribosomal proteins have been shown to be nonessential in B. subtilis, at least for cell proliferation. Although several mutants that harbored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 64 publications
(92 reference statements)
7
102
0
1
Order By: Relevance
“…It was recently shown that the deletion of the rpsU gene (encoding the S21 ribosomal protein) led to the formation of a small circle of a swarm colony (Akanuma et al, 2012). To assess the effect of rrn copy number on motility, we measured the swarm circles for the ten strains on LB agar plates containing 0.4 % Bacto agar.…”
Section: Motility Of Cells Carrying One To Ten Copies Of the Rrn Operonmentioning
confidence: 99%
“…It was recently shown that the deletion of the rpsU gene (encoding the S21 ribosomal protein) led to the formation of a small circle of a swarm colony (Akanuma et al, 2012). To assess the effect of rrn copy number on motility, we measured the swarm circles for the ten strains on LB agar plates containing 0.4 % Bacto agar.…”
Section: Motility Of Cells Carrying One To Ten Copies Of the Rrn Operonmentioning
confidence: 99%
“…In bacteria, the severity of the growth phenotypes of ribosomal mutants can depend strongly on the growth conditions, especially the growth temperature (Akanuma et al, 2012). Therefore, we tested the Drps15/Drpl33 double knockout for survival under different temperatures.…”
Section: Rescue Of the Synthetic Lethality Of The Drps15/drpl33 Doublmentioning
confidence: 99%
“…First, we confirmed the essentiality of rpsU and rpsK for cell growth. We successfully created a mutant in which the rpsU-yqeY operon was deleted by replacing these two open reading frames with an antibiotic-resistance cassette (NBS1513); however, compared to a previous study, 31) rpsK was not deleted in this mutant. We concluded that rpsK but not rpsU was essential for cell growth using rpsK-and rpsU-inducible strains (NBS1533 and NBS1530, Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%